PENYULUHAN SKRINING GIZI DASAR SECARA MANDIRI BERBASIS KECERDASAN BUATAN MACHINE LEARNING PADA SISWA SMA - Imam Syafii; Alfan Ridha; Vioresta Steffiandry; Rafli Yunan Suryatama (Politeknik Negeri Sriwijaya, 2023)
Nutritional status is an indicator of success in meeting nutritional needs, especially shown in achieving weight according to age. Good nutritional status if the nutritional intake is in accordance with the needs of the body. Lack of nutrient intake in food can cause malnutrition, while excess nutrient intake will result in over nutrition. Lack of knowledge related to nutritional status has an impact on body growth and development. Providing nutritional status analysis can involve technology in the form of artificial intelligence. Data processing related to cases that have occurred before in technology using machine learning. Application of technology in providing web-based nutritional status screening analysis. The application of technology has an effect in action in the form of providing fast and accurate analysis and can provide suggestions for reducing the impact on the occurrence of illness and death associated with nutritional status.